2015
DOI: 10.1007/s11010-015-2392-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of nitric oxide/soluble guanylyl cyclase pathway in ascorbic acid-mediated protection against acute kidney injury in rats

Abstract: The present study investigated the possible involvement of nitric oxide/soluble guanylyl cyclase (NO/sGC) pathway in ascorbic acid (AA)-mediated protection against acute kidney injury (AKI) in rats. The rats were subjected to bilateral renal ischemia by occluding renal pedicles for 40 min followed by reperfusion for 24 h. The AKI was assessed in terms of measuring creatinine clearance (CrCl), blood urea nitrogen (BUN), plasma uric acid, potassium level, fractional excretion of sodium (FeNa), and microproteinur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…A study by Koul et al that employed a rat model concluded that ascorbic acid protects against IRinduced acute kidney injury (38). Similar studies to ours have shown the protective role of vitamins C and E in attenuating oxidative stress following renal ischemia in a rat model (39), probably by radical scavenging and expressing antioxidant properties (40).…”
Section: Discussionsupporting
confidence: 82%
“…A study by Koul et al that employed a rat model concluded that ascorbic acid protects against IRinduced acute kidney injury (38). Similar studies to ours have shown the protective role of vitamins C and E in attenuating oxidative stress following renal ischemia in a rat model (39), probably by radical scavenging and expressing antioxidant properties (40).…”
Section: Discussionsupporting
confidence: 82%
“…Recently, research has mainly focused on miR-98 regulation of apoptosis and its target proteins including Bcl-2, Fas, caspase-3, and c-Myc ( 50 53 ). Expression of miR-98 was downregulated in osteoarthritis (OA) cartilage tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Some animal AKI studies have compared the effect of l -arginine (NO donor) and vitamin C supplementation on biomarkers of lipid, DNA and protein oxidation, and kidney function, and have demonstrated superior protection afforded by vitamin C [ 86 , 138 ]. These improvements in renal function and oxidative stress markers in I/R-induced AKI in rats, may involve NO/soluble guanylyl cyclase (cGC), as inhibitors of this pathway ( L -NAME and methylene blue) reduced the reno-protective effects of vitamin C [ 82 ]. Further, ascorbate increased tissue GSH and nitrate/nitrite levels, suggesting a preservation of NO • levels.…”
Section: Vitamin C and Renal Protectionmentioning
confidence: 99%